2012
DOI: 10.1016/j.asr.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hindlimb unloading and partial weight suspension models for spaceflight-type condition induced effects on white blood cells

Abstract: Animal models are frequently used to assist in the determination of the long- and short-term effects of space flight. The space environment, including microgravity, can impact many physiological and immunological system parameters. It has been found that ground based models of microgravity produce changes in white blood cell counts, which negatively affects immunologic function. As part of the Center of Acute Radiation Research (CARR), we compared the acute effects on white blood cell parameters induced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Previously, we have shown that blood cell counts vary within the first 48 hours of exposure to HU, after which time the counts are not different in a statistically significant manner, compared to the non-suspended controls. The changes in blood cell counts is presumably attributed to stress of the HU system [29]. To study an “acute” time point after radiation +/− HU treatment, a 4 day time point was chosen so that the initial stress response to the suspension system would be minimized.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that blood cell counts vary within the first 48 hours of exposure to HU, after which time the counts are not different in a statistically significant manner, compared to the non-suspended controls. The changes in blood cell counts is presumably attributed to stress of the HU system [29]. To study an “acute” time point after radiation +/− HU treatment, a 4 day time point was chosen so that the initial stress response to the suspension system would be minimized.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, several experiments have been performed to determine the effects of simulated microgravity on blood cell counts with or without additional exposure to space radiation [e.g., (148)]. To evaluate the impact of hypogravity on the effect of SPE radiation on immunological function, experiments were performed with 6–8 week old female ICR mice that were irradiated with 0.5, 1 or 2 Gy of γ-rays with or without hypogravity simulated using the PWS model, described by Wagner et al (149).…”
Section: Acute Radiation Effectsmentioning
confidence: 99%
“…Numerous studies have been performed to evaluate the effects of SPE radiation on the immune system as a part of research on the acute risks of SPE radiation exposure (138, 144,148, 151, 152). Many of the SPE radiation studies were performed with and without microgravity simulated with PWS or HS (134, 138,148, 151153).…”
Section: Acute Radiation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed manned-missions by the National Aeronautics Space Administration (NASA) to the surface of Mars have led to concerns about the effects of a three-year mission on astronaut health (Badhwar et al 1992), with the most serious concerns involving the potential biological consequences of exposure to space radiation and prolonged exposure to microgravity (Cucinotta et al 2001, Mognato et al 2009, Wilson et al 2012). On a mission to Mars, astronauts will be exposed to background levels of highly energetic, charged particles known as HZE particles and solar particle event (SPE) radiation (Hellweg and Baumstark-Khan 2007).…”
Section: Introductionmentioning
confidence: 99%